Cuentas por pagar y su incidencia en los proveedores de la unidad de hemodiálisis de la provincia de Los Ríos, periodo 2021. - Moran Mendoza, Azlie Rousse (2023)
During the 2021 period, the Hemodialysis Unit of Los Rios Province has faced challenges in managing its accounts payable to suppliers. Due to the pandemic and other external factors, the Unit has had difficulty meeting the payment deadlines agreed with its suppliers, which has led to an increase in outstanding debts. In addition, Unit staff have raised concerns about the quality of services provided and the lack of resources to address these issues. The Hemodialysis Unit of Los Rios Province has maintained a constant flow of accounts payable to suppliers, mainly for the purchase of medical supplies and equipment necessary to carry out patient treatments. Despite the efforts to keep payments up to date, there have been some difficulties that have caused delays in payments and have generated concern among suppliers.